Effect of hydrolytic enzymes pretreatment on the oil extraction from pumpkin seeds - Nosenko, Tamara; Vovk, Hanna O.; Korolyuk, Tamara (My University, 2019)
Introduction. Enzyme assisted technologies were proposed for oil seeds processing. Currently there are no reports about pumpkin seeds oil recovering using enzyme assisted pretreatment. The aim of the present study was to evaluate the effect of enzyme mixture on the cell integrity, oil yield of cold-pressing and dynamics of solvent extraction of pumpkin seeds oil. Materials and Methods. Protolad, Alkaline, acid proteases and Cellulad (ENZIME, Ukraine) were used for pumpkin seeds pretreatment. The cells integrity was evaluated by the method of immediate "shaking". The cold pressing was carried out on the laboratory screw press. The solvent oil extraction rate was estimated using a Soxhlet extractor as oil quantity extracted after one extraction cycle. Results and discussion. It was detected that main increase of pumpkin seed cells integrity destruction comparing with a control sample had been happened after 2-hour of enzyme pretreatment. Further incubation of ground seeds with enzymes did not lead to significant increase of "open" cells content in the mixture. It was shown that using of different kind of proteolitic enzymes for pumpkin seeds pretreatment resulted in increase of destroyed cells quantity from 3 to 10.4 %. Using of proteases and cellulase mixture for pumpkin seeds pretreatment had resulted in further increase of level of pumpkin seed cells "revealing" by 10 %. The oil yield of cold pressed pumpkin oil after enzyme pretreatment with protease (70 %) and cellulase (30 %) mixture was increased from 62.3 (control sample) to 70.0 % from total oil content of seeds. The rate of solvent extraction of oil from pumpkin seeds had increased after enzyme pretreatment, that means 25.4 and 17.7 % of oil were extracted after 80 min extraction from mass of enzyme pretreated and control seeds, respectively. There was no difference of peroxide content between enzyme pretreated sample and control. Conclusions. Using of proteases and cellulases mixture for pumpkin seeds pretreatment had resulted in increase of destroyed cells quantity, following by increase of cold pressed pumpkin oil as well as rate of solvent extraction of oil from pumpkin seeds.
Keywords: кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; холодне пресування; seed fermentation; ферментація насіння; pumpkin oil; олія гарбуза; гарбузове насіння